2014
DOI: 10.1002/2013jc009759
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the barrier layer thickness in the Indian Ocean using Aquarius Salinity

Abstract: Monthly barrier layer thickness (BLT) estimates are derived from satellite measurements using a multilinear regression model (MRM) within the Indian Ocean. Sea surface salinity (SSS) from the recently launched Soil Moisture and Ocean Salinity (SMOS) and Aquarius SAC-D salinity missions are utilized to estimate the BLT. The MRM relates BLT to sea surface salinity (SSS), sea surface temperature (SST), and sea surface height anomalies (SSHA). Three regions where the BLT variability is most rigorous are selected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 40 publications
5
34
0
Order By: Relevance
“…These authors reported that the BLT attains its annual maximum during February, but in present study the annual BLT maximum is observed in January. The spatial distribution pattern of Thadathil et al () and Felton et al (), however, closely resembles the pattern obtained in the present study for April, May, and June.…”
Section: Resultssupporting
confidence: 91%
“…These authors reported that the BLT attains its annual maximum during February, but in present study the annual BLT maximum is observed in January. The spatial distribution pattern of Thadathil et al () and Felton et al (), however, closely resembles the pattern obtained in the present study for April, May, and June.…”
Section: Resultssupporting
confidence: 91%
“…Insufficient model resolution precludes some physical processes. Particularly, observed salinity profile is of complicated structure near the sea surface [e.g., Felton et al ., ; Song et al ., ; Drushka et al ., ], which cannot be properly reproduced by the present vertical resolution (∼2.9 m for the top layer). In addition, mesoscale eddies and submesoscale filaments are also important in modulating intraseasonal salinity variability in the far northern part of the bay [ Parampil et al ., ; Sengupta et al ., ], requiring finer horizontal and vertical resolutions to take into account.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Fresh water is dispersed southwards by surface currents along both coasts and by gradual mixing with saltier waters below (Behara and Vinayachandran 2016;Benshila et al 2014;Shetye 1993). The mixing process is slow and in the post-monsoon season fresh water creates a thin layer of low salinity at the sea surface, overlying the constant-temperature layer below (Felton et al 2014;Vinayachandran et al 2002). The warm but saltier water below the surface layer is often referred to as the barrier layer because it inhibits convection and so restricts the vertical mixing of water and heat flow to the deeper water column.…”
Section: Water Structure Circulation and Productivitymentioning
confidence: 99%